Application of Diabetic Foot Spa Procedure to Optimize Foot Function Post-Creating Diabetic Foot Ulcer - Idramsyah Idramsyah; Bella Samya Dwi Putri; Rahma Annisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to provide an overview of the application of diabetic foot spa procedures to optimize foot function after healing diabetic foot wounds. This qualitative research method uses a descriptive case study design. The results of the study indicate that the diabetic foot spa procedure can be applied to people with diabetes mellitus by using therapeutic communication stages which consist of a pre-interaction phase for conducting assessments, diagnoses, and learning action procedures. The introduction orientation phase builds trusting relationships, explanations of actions, and approval of activities. The interaction phase is to carry out the preparation of equipment, environment, patients, and nurses, as well as all implementation of action procedures, and the termination phase is for evaluation, as well as future contracts and follow-up plans. In conclusion, diabetic foot spa can be used as a nursing intervention in foot care to fulfill security and protection needs, focusing on nursing problems and the risk of disrupting skin/tissue integrity. Keywords: Diabetic Wounds, Diabetic Foot Disease, Foot Spa Treatment Procedures